Abdominal vessel depiction on virtual triphasic spectral detector CT: initial clinical experience - Lennartz, Simon; Laukamp, Kai Roman; Tandon, Yasmeen; Jordan, Michelle; Große Hokamp, Nils; Zopfs, David; Pennig, Lenhard; Obmann, Markus; Gilkeson, Robert C.; Herrmann, Karin A.; Ramaiya, Nikhil; Gupta, Amit (Abdominal imaging, 2021)
Purpose To evaluate vessel assessment in virtual monoenergetic images (VMI 40keV ) and virtual-non-contrast images (VNC) derived from venous phase spectral detector computed tomography (SDCT) acquisitions in comparison to arterial phase and true non-contrast (TNC) images. Methods Triphasic abdominal SDCT was performed in 25 patients including TNC, arterial and venous phase. VMI 40keV and VNC were reconstructed from the venous phase and compared to conventional arterial-phase images (CI art ), TNC and conventional venous-phase images (CI ven ). Vessel contrast and virtual contrast removal were analyzed with region-of-interest-based measurements and in a qualitative assessment. Results Quantitative analysis revealed no significant attenuation differences between TNC and VNC in arterial vessels ( p -range 0.07–0.47) except for the renal artery ( p = 0.011). For venous vessels, significant differences between TNC and VNC were found for all veins ( p < 0.001) except the inferior vena cava ( p = 0.26), yet these differences remained within a 10 HU range in most patients. No significant attenuation differences were found between CI art /VMI 40keV in arterial vessels ( p -range 0.06–0.86). Contrast-to-noise ratio provided by VMI 40keV and CI art was equivalent for all arterial vessels assessed ( p -range 0.14–0.91). Qualitatively, VMI 40keV showed similar enhancement of abdominal and pelvic arteries as CI art and VNC were rated comparable to TNC. Conclusion Our study suggests that VNC and VMI 40keV derived from single venous-phase SDCT offer comparable assessment of major abdominal vessels as provided by routine triphasic examinations, if no dynamic contrast information is required.